Computing and Network Sustainability Proceedings of IRSCNS 2018 - Peng, Sheng-Lung; Dey, Nilanjan; Bundele, Mahesh (Lecture Notes in Networks and Systems, 2019)
This book offers a compilation of technical papers presented at the International Research Symposium on Computing and Network Sustainability (IRSCNS 2018) held in Goa, India on 30-31st August 2018. It covers areas such as sustainable computing and security, sustainable systems and technologies, sustainable methodologies and applications, sustainable networks applications and solutions, user-centered services and systems and mobile data management. Presenting novel and recent technologies, it is a valuable resource for researchers and industry professionals alike.